The Location Privacy Protection Technology of Mobile Intelligent Terminal - LI Zhi-peng; SUN Ming-song; SONG Zeng-lin (Journal of Harbin University of Science and Technology)
To solve the problems of users’ personal location privacy are facing great threat in the era of big data，according to the theory of location big data，the shortcomings of existing location privacy protection technology are analyzed from the perspective of users’ mobile intelligent terminals. Based on the existing encryption and distortion algorithm models，it introduces a coordinate transformation method，increases fragmentation of user location information，and optimizes the technologies of dummies and false-name. In simulation experiments，a large number of user trajectories are generated by simulation software，and the information entropy of improved and original algorithm is studied to demonstrate the superiority of the improved algorithm. The experimental results verify that the improved encryption and distortion algorithm is more effective to protect personal location privacy information.